Social Factors Affecting Recidivism Among Ex-Convicts in Nigeria - Ahmed, Adamu; Modibbo, Nafiu Abubakar; Habila, Ibome Bulmen (NIU Journal of Social Sciences; Vol 11 No 3 (2025): NIU Journal of Social Sciences, Vol. 11 No. 3, September 2025DO - 10.58709/niujss.v11i3.2487, 2025)
Recidivism, the consistent return of ex-prisoners to offences, persists in Nigeria, reflecting the structural defects in the nation’s criminal justice and correctional services. The study attempts to examine the nature and extent of recidivism in the light of the services provided by the Nigerian correctional services in terms of reformation and rehabilitation. It is a systematic content analysis studious the use of secondary data in making conclusions. High recidivism is indicative of other issues, including insufficient rehabilitation programs, social stigmas, and economic struggles ex-felons have after they leave prison. This research examines the various elements leading to recidivism in Nigeria underscore the role of prison rehabilitation, unemployment, peer pressure, and lack of a support system. In these correction facilities, effective vocational training and psychological aid are relatively absent, so ex-prisoners are poorly equipped to enter the workforce. Furthermore, the negative effect of the stigma attached to having a criminal record, combined with the difficulty of obtaining stable employment, is an important contributor to habitual offending. Factors of peer and reintegrative effects of ex-convicts also make the problem worse. Building on Agnew's General Strain Theory, the current study connects strain (e.g., unemployment, rejection, and social support deprivation) with higher recidivism. The study suggests that widespread reform is needed, such as improved rehabilitation programs, public consciousness drives to reduce stigma, job assistance, and greater support systems for post-release, to fully facilitate a successful reintegration. The solution to these factors is important to reducing the recurrence of criminals, making Nigeria safe, and building an all-embracing society. Keywords: Social Degradation, Recidivism, and Ex-convicts.